Genotype-environment interaction of yield in yellow corn hybrids, using AMMI and SREG - Ponce-Encinas, María Corina; López-Morales, Fernando; Chura-Chuquija, Julián; Hernández-Leal, Enrique; Hernández-Salinas, Gregorio; Aragón-García, Agustín (Revista Mexicana de Ciencias Agrícolas, 2022)
It is indispensable for corn (Zea mays L.) plant breeding programs to select homogeneous materials, with high yield and with stable agronomic attributes; also, that they have a good adaptability in contrasting environments. The objective of the work was to evaluate the stability and genotype-environment interaction of the yield of 36 hard yellow corn hybrids, evaluated in seven environments of Peru, during 2016-2018, these materials were analyzed using the AMMI (additive main effects and multiplicative interaction) and SREG (site regression) models. The design used in each experiment was a 6×6 lattice with three repetitions, and the response variable was grain yield. A combined analysis of variance was performed, in which statistical differences between them (p≤ 0.05) were detected, then the Tukey mean test (p≤ 0.05) was applied, finally the AMMI and SREG models were run and the biplot graphs of each statistical model were obtained. Of the interaction between PC1 and PC2, AMMI explained 45.5% and 15.3%, respectively, and SREG with 59.8% and 12.2%, for the same components. The trilinear hybrids Dk-5005 and AG-01 outperformed the double-cross hybrids. The AMMI model detected the existing GE interaction in grain yield, and the SREG accurately grouped the assessment sites into six mega-environments. The three environments of La Molina and that of Huánuco identified the two hybrids (Dk-5005 and AG-01) with the highest grain yield (11.524 and 11.359 t ha-1, respectively).
Keywords: Zea mays; biplot graph; double and trilinear hybrids; stability and adaptability